I am not asking PM to resign, says Mahathir - Daily Express, (KK) (Daily Express, 2014)
KUALA LUMPUR: Tun Dr Mahathir Mohamad said his criticism against Datuk Seri Najib Razak was not personal and it did not mean that the Prime Minister should resign from his post.